Dissociation between schizophrenia-relevant behavioral profiles and volumetric brain measures after long-lasting social isolation in Roman rats. (June 2020) - Sánchez-González, A.; Oliveras, I.; Río-Álamos, C.; Piludu, MA.; Gerbolés, C.; Tapias-Espinosa, C.; Tobeña, A.; Aznar, S.; Fernández-Teruel, A.
Highlights: Long-lasting social isolation effects have been tested in the Roman rats. Social isolation produces divergent effects in RHA-I vs RLA-I rats. RHA-I rats show PPI deficits, anxiety and hyperactivity induced by social isolation. Social isolation differentially impairs spatial memory in the Roman strains. Long-lasting social isolation produces an increment in volume of mPFC. Abstract: Social isolation rearing of rodents is an environmental manipulation known to induce or potentiate psychotic-like symptoms and attentional and cognitive impairments relevant for schizophrenia. When subjected to a 28-week isolation rearing treatment, the Roman high-avoidance (RHA-I) rats display the common behavioral social isolation syndrome, with prepulse inhibition (PPI) deficits, hyperactivity, increased anxiety responses and learning/memory impairments when compared to their low-avoidance (RLA-I) counterparts. These results add face validity to the RHA-I rats as an animal model for schizophrenia-relevant behavioral and cognitive profiles and confirm previous results. The aim here was to further investigate the neuroanatomical effects of the isolation rearing, estimated through volume differences in medial prefrontal cortex (mPFC), dorsal striatum (dSt) and hippocampus (HPC). Results showed a global increase in volume in the mPFC in the isolated rats of both strains, as well as strain effects (RLA > RHA) in the three brain regions. These unexpected but robust results, might have unveiled some kind of compensatory mechanisms due to the particularly long-lasting isolation rearing period, much longer than those commonly used in the literature (which usually range from 4 to 12 weeks).